INOVASI TEKNOLOGI DIGITAL DALAM MENINGKATKAN KUALITAS PEMBELAJARAN: SYSTEMATICA LITERATURE REVIEW - Rina Nurhidayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study is to conduct a literature review related to articles with the theme of the use of digital learning media in science learning. This type of research uses a literature study method to examine the use of digital technology in learning. Data collection was carried out by collecting and reviewing articles related to digital learning media in science learning published in 2020-2024. Researchers collected 30 articles in journals from Google Scholar using Publish or Perish Software. Based on the results of a systematic review of several published studies, it can be concluded that various types of digital media can be used in science learning activities. The learning media that are widely used are digital media in the form of images, videos, simulations and interactive games. In addition, the use of digital learning media in science learning can improve student learning outcomes, student learning motivation and students' digital literacy skills. Not only that, the use of science learning media is also effective and efficient when integrated into the learning model. The results of this study indicate that learning innovation is important to improve student learning outcomes in the digital era.